A Caligrafia de Deus e a cidade ilhada: imagens da cidade de Manaus na contística de Márcio Souza e Milton Hatoum - Rincon, Neire Márzia (2012)
This study analyzes the books of short stories The handwriting of God (1994), Marcio Souza, and Islanded city (2009), Milton Hatoum, to see how the city of Manaus is represented by two Amazonian writers. The metaphors that enable reading of the town are the crystal, the flame and the city mouse, systematized concepts by Italo Calvino (1990) and Renato Gomes Cordeiro (2008), the mappings proposed by Kevin Lynch (1999) and the steps practitioners of the characters of the town suggested by Michel de Certeau (2009). The analyzes undertaken in stories demonstrate that there similarities and differences between Márcio Souza and Milton Hatoum provide readability in the way the city of Manaus in the literary text, for while the former builds tableaux of Manaus seen by various senses (visual, sensory, olfactory and taste), the second represents the urban area of Manaus evoked by memories of the narrators.